Electromagnetic Landau Resonance: MMS Observations - Z.‐Y. Liu; Q.‐G. Zong; Y.‐F. Wang; X.‐Z. Zhou; S. Wang; J.‐H. Li (Geophysical Research Letters)
Abstract Theoretical analysis has revealed a specific resonance that shares the same condition as Landau resonance, but instead involves wave electromagnetic fields rather than traditionally electrostatic fields. While this resonance, referred to as electromagnetic Landau resonance due to its properties, is considered significant for magnetospheric dynamics, rare reports or evaluations based on observations have been made thus far. Here, we present an event detected by the Magnetospheric Multiscale mission near the dayside magnetopause. During this event, ∼748‐eV protons are observed to be in resonance with a wave. Detailed data analysis demonstrates the resonant velocity closely matches the wave's parallel phase speed, which, combined with the significant work done by wave perpendicular electric field, confirms this interaction as electromagnetic Landau resonance. Further investigation indicates these protons are being secularly accelerated within this resonance. Consequently, our observations provide the first empirical evidence supporting the previously suggested theoretical importance of the electromagnetic Landau resonance.